Santri trained troops: Making new normal kits and training for the COVID-19 task force - Damayanti, Meta Maulida; Yuniarti, Yuniarti; Rachmawati, Meike; Kusmiati, Mia (University of Merdeka Malang, 2022)
Since the COVID-19 pandemic first emerged in December 2019 and was confirmed in Indonesia in March 2020, the Indonesian government has imposed a strict lockdown. The number of confirmed cases is increasing all the time. Efforts to prevent transmission must be carried out immediately, including improving health protocols. The activity aims to create trained troops Santri, by providing insight into COVID-19 which consists of training to implement health protocols and soft skills for making new normal kits, namely hand sanitizers and cloth masks. The activities were carried out at the Manarul Huda Islamic Boarding School, Bandung to 31 Santri. The new normal kit manufacturing training is accompanied by an expert. The training of Santri produces cadres with a level of knowledge about COVID-19 most highly with a fair category (51,61%). Based on the percentage of the group, age17 years, male gender, and education level graduated from school have a higher level of good knowledge than other groups. This service activity produces trained troops Santri equipped with knowledge about COVID-19 particularly good health protocols, has soft skills to make hand sanitizers and cloth masks. Towards they can produce a new normal kit and create a COVID-free Islamic boarding school area.